Does self-access learning enhance students’ motivation and participation in classroom activities? / Ellis Amit - Amit, Ellis (2004)
The study undertaken is indeed an effort to find out how Self-Access Learning can help to enhance the students' motivation and participation in classroom activities. The purpose of the study is to find out the effectiveness of Self-Access Learning in giving motivation to the students regarding their active participation in classroom activity. In an attempt to obtain the data, a questionnaire which comprises of 25 questions was administered on 84 students. The students were from the Non Self-Access learning Group and the Self-Access Learning Group. The findings in the form of students' responses to the items of the questions were analyzed by comparing both groups to get the information about their interests in learning English. The researcher hope to share the findings with any interested any interested individual, especially educators of English Language to reflect their teaching techniques, methods and approaches. It is hope that the findings of the study will provide meaningful academic sources for language teachers to gain some knowledge and personal insight growth.